Respuesta :
Answer:
[tex]y=2(\frac{1}{2} )^x[/tex]
Step-by-step explanation:
Given the exponential function as
[tex]y=ab^x[/tex]
substitute both points in the equation above
point (-3,16) will be
[tex]16=ab^{-3}[/tex]
point (-1,4) will be
[tex]4=ab^{-1}[/tex]
make a the subject of the formula in both equations above
[tex]a=\frac{16}{b^{-3} } \\\\\\a=\frac{4}{b^{-1} }[/tex]
This means
[tex]=\frac{16}{b^{-3} } =\frac{4}{b^{-1} }[/tex]
Cross multiply as;
[tex]16b^{-1} =4b^{-3}[/tex]
Divide by 4 both sides to get
[tex]4b^{-1} =b^{-3}[/tex]
Divide by b^-1 both sides
[tex]\frac{4b^{-1} }{b^{-1} } =\frac{4b^{-3} }{b^{-1} } \\\\\\4=b^{-2} \\\\\\4=\frac{1}{b^2} \\\\\\b^2=\frac{1}{4} \\\\\\b=\sqrt{\frac{1}{4} } =\frac{1}{2}[/tex]
Find value of a
[tex]4=ab^{-1} \\\\4=a*(\frac{1}{2})^{-1} \\\\\\4=a*2\\\\2=a[/tex]
Hence
a=2 and b=1/2 thus write the equation as;
[tex]y=ab^x\\\\\\y=2(\frac{1}{2} )^x[/tex]